Menuju Ekonomi Hijau Yang Berkelanjutan: Tantangan Dan Peluang Untuk Stabilitas Lingkungan Dan Ekonomi Jangka Panjang - Firdiana Nur Auliya; Nurhadi Nurhadi (Jurnal Pengabdian Masyarakat Nusantara, 2023)
This journal discusses the problems and prospects associated with realizing a sustainable green economy in an effort to achieve long-term economic and environmental stability. Dependence on fossil energy, pollution and poor waste management are the problems. However, supportive public policies, green industry development, and technological advances for renewable energy open up opportunities. Renewable energy, sustainable transportation and waste management are areas that can generate long-term economic and environmental benefits. This research provides insights for stakeholders to implement green economic practices, which will generate long-term benefits such as better environmental quality, economic resilience, and community welfare. To achieve the goals of sustainable development and to build an eco-friendly and sustainable economy for future generations, all parties must work together.